DOI: 10.31274/rtd-180813-15682
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic specialization in Puccinia coronata avenae (Corda) Eriks and Henn

Abstract: The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleedthrough, substandard margins, and improper alignment can adversely affect reproduction.In the unlikely event that the author did not send UMI a complete manuscript and there are missing pages, these will be noted. Also, if unauthorized copyright material had to be removed, a note will indicate the deletion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
2
2

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 0 publications
2
50
2
2
Order By: Relevance
“…In general, younger leaves on the same plant are as susceptible as seedlings, but the older leaves are resistant (Hassebrauk, 1932;Newton and Brown, 1934;Murphy, 1935)* These observations are contrary to what had been reported for leaf rust of wheat (Johnston and Melchers,I929). Simons (1961) reported that some cultlvars of oats were resistant as adult plants to certain races of crown rust but susceptible to others.…”
Section: Mature-plant Resistancecontrasting
confidence: 56%
See 2 more Smart Citations
“…In general, younger leaves on the same plant are as susceptible as seedlings, but the older leaves are resistant (Hassebrauk, 1932;Newton and Brown, 1934;Murphy, 1935)* These observations are contrary to what had been reported for leaf rust of wheat (Johnston and Melchers,I929). Simons (1961) reported that some cultlvars of oats were resistant as adult plants to certain races of crown rust but susceptible to others.…”
Section: Mature-plant Resistancecontrasting
confidence: 56%
“…Shortening of the incubation period at higher temperatures has been well documented (Marland, 1937;Peturson, 1930)• Shifts in infection type at higher temperatures are not un common (Murphy, 1935;Saari and Moore, 1962;Simons, 195^;Putrell and Rivers, 1955). The fundamental reactions in the breakdown of resistance are unknown; however, at least three schools of thought prevail: carbohydrate metabolism, in hibitory mechanisms, and molecular aspects of temperature response.…”
Section: Shift In Infection Type Due To Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…The seedlings were then placed in a misting chamber at room temperature for 24 hours, and later transferred to a growth room maintained at 23˚C. Two weeks later, seedlings were scored for crown rust response using an IT scale of "0"-"4" described by Murphy (1935), with minor modifications (refer Cabral and Park, 2014). While IT scores between "0" and "2" were considered resistant, those between "2-3" and "3" were indicative of moderate resistance, and scores of "3-3+" and "3+" indicated susceptibility.…”
Section: Seedling Inoculation and Disease Scoringmentioning
confidence: 99%
“…Hagborg (1971) was determined by summing the products of, the number of disease lesions and the infection type, 0 to 3 as described by Murphy (1935 For personal use only. As mentioned previously (Hagborg 1970 (Spiertz 1973 …”
mentioning
confidence: 99%